PERSEPSI PEMUKA AGAMA BUDDHA MENGENAI EKSKLUSIVISME SEKTARIAN DALAM AGAMA BUDDHA - Madiyono Madiyono (Jurnal Ilmiah Kampus: Sati Sampajanna, 2019)
This article is the result of a study that began with increasing of the „identity politics‟, whichemphasizes the role of a religion to achieve politics goals, assuming only one religion is the mostcorrect while the others religions is wrong. In internal aspect of religion, it is considered as a sectarianexclusivism which considers anly one sect to be completely right, other sects is wrong. Within theBuddhist community, sectarian exclusivism hypothesized still exists. Although it does not causephysical disputes between people, an exclusive attitude can hamper the process of preservation anddevelopment of Buddhism. From these considerations, a study was conducted to find out theperceptions of Buddhist leaders in Jakarta and Tangerang regarding exclusivism in Buddhism. Thisresearch is a descriptive qualitative study by case study approach. The data collected was analyzedusing the Miles and Huberman model, through data collected, reduction, display and verification orconclusions. Credibility data was carried out by triangulation, member checks, discussions with peers,and also extension of research time. From the results of the study it could be concluded that Buddhistleaders perceive that internal exclusivism is still needed and important for the existence ofsects/assemblies because it describes the characteristics, identity associated with one sect with anotherthat is suitable for increasing faith to Triple Gem. External exclusivism with assuming the only one isthe truest, the best, the purest and consider the others were wrong is unnecessarily because they onlycause dispute and hinder the development of Buddhism. Factors that cause sectarian exclusivism inBuddhism are associated with assumptions that if there is no internal sectarian exclusive attitudeseroded traditions that have been bequeathed by ancestors, the egos of leaders, and different perspectiveand leadership paradigm regarding Buddhism. Positive values of sectarian exclusive attitudes arestrengthening the faith of the people to the truth (Dhamma), maintaining the traditions of each sectsthat show the identity, and the characteristics of each sects. The negative values of exclusivism arepotentially making dispute in communities due to mutual disdain, assume their sect is the easiest, thebest, the purest and considers as the only truest sect. Efforts are made to reduce the impact of sectarianexclusivism in Buddhism by holding a joint Vesak celebration, joint social activities, such as socialservices, joint Health Walks Program; strengthen the role of non-sect organizations that can unifyBuddhists such as the Banten Buddhist Forum (FUB), Gemabudhi, and the Indonesian BuddhistReligious Council Association (Permabudhi).